ESENSI PENGALAMAN PARA PELAKU DUNIA FOTOGRAFI - Putri Wulandari; Nuriyatul Lailiyah (Interaksi Online, 2019)
Photography appears to reach the goal of objectivity, because it is believed to be able to expose visual reality. One type of commercial photography that has a fairly high appeal is fashion photography or model photography. The experience gained from the world of photography is quite diverse, a lot of people are starting to take interest in becoming photographers and models because of their fondness of taking and to be taken picture of. However, being a model and photographer is also not always going well, there are many problems regarding bad experience and media coverage that vilify the model profession and photographer. This problem arises because there is no openness and closeness between the model and the photographer. The method used in this study is qualitative research with phenomenological approaches. The purpose of this study is to describe the essence of the party's experience in photography. The theory used in this study is Phenomenology and Self Disclosure. The finding in this study indicates that the main reason for the models in choosing their job is money. While the photographer’s reasons are pleasure or hobby and passion that is within the photographer. Then, the bad experience felt by the model was produced through the unpleasant treatment obtained from the photographer. And when the model got the unpleasant treatment, the thing that the model did was trying to be professional. This unpleasant treatment received from the photographer resulted in a traumatic experience to the model. Meanwhile, the unpleasant experiences felt by the photographer were when the model was often late to come to the location of the photo session and when faced with a model which had a bad attitude. Furthermore, when doing a model selection, the criteria that usually used by photographers are their physical appearance, models that have ideal posture and are pleasing to the eye. The closeness experienced by the model and photographer will form an impressive experience felt by the model. And the closeness that exists between the two will also determine the good and bad results of the photos. The conclusion in this study is that bad relationships will occur if there is no communication between the photographer and the model, because there is no openness generated from communication, then closeness will not occur and there will be no good experience created between the two, even the results of the photos will also be bad if there is no chemistry between the model and the photographer.